Odpowiedzi

2010-02-28T15:58:45+01:00
½ab - ¾a² + 3¾ ab - 1,5a² + 5/8 a ² = 1/2ab-3/4 a²+15/4ab-15/10a²+5/8a²=-3/4 a²-15/10a²+5/8a²+1/2ab+15/4ab= -60/80a-120/80a²+50/80a²+2/4ab+15/4ab=-130/80a²+17/4ab

1,2a - 2/3 a² + 0,75 - 1 3/8 a - ½ + 2/9 a ² =
- 2/3 a²+ 2/9 a ²+1,2a - 1 3/8 a+ 0,75 - ½ =
-6/9a²+2/9a²+12/10a-11/8a+3/4-1/2= -4/9a²+48/40a-55/40a+3/4-2/4=-4/9a²+7/40a+1/4

2010-02-28T15:59:27+01:00
½ab - ¾a² + 3¾ ab - 1,5a² + pięć ósmych a ² =
4,25ab-1⅝a²

1,2a - dwie trzecie a² + 0,75 - 1 i trzy ósme a - ½ + dwie dziewiąte a ² =
7/40a-4/9a²+0,25